2017
DOI: 10.1016/j.jvs.2017.01.026
|View full text |Cite
|
Sign up to set email alerts
|

The impact of endovascular repair on management and outcome of ruptured thoracic aortic aneurysms

Abstract: Introduction Endovascular repair (TEVAR) has become an alternative to open repair for the treatment of ruptured thoracic aortic aneurysms (rTAA). The aim of this study was to assess national trends in the utilization of TEVAR for the treatment of rTAA and determine its impact on perioperative outcomes. Methods Patients admitted with a ruptured thoracic aortic aneurysm between 1993 and 2012 were identified from the Nationwide Inpatient Sample (NIS). Patients were grouped in accordance with their treatment: TE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
18
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 32 publications
2
18
0
1
Order By: Relevance
“…Following the implementation of TEVAR, mortality decreased by 10% (from 36% to 27%). 33 The current analysis reveals that in hospital mortality after rDTA aneurysm repair shows a high variability over time, and ranges between 34.7% and 20.2%. In contrast, mortality rates for nrDTA aneurysm cases are bisected (9.4% in 2005 down to 4.2% in 2014).…”
Section: Discussionmentioning
confidence: 80%
“…Following the implementation of TEVAR, mortality decreased by 10% (from 36% to 27%). 33 The current analysis reveals that in hospital mortality after rDTA aneurysm repair shows a high variability over time, and ranges between 34.7% and 20.2%. In contrast, mortality rates for nrDTA aneurysm cases are bisected (9.4% in 2005 down to 4.2% in 2014).…”
Section: Discussionmentioning
confidence: 80%
“…In addition, to separate ascending from descending thoracic aneurysms, patients who underwent cardiopulmonary bypass during the same hospital stay were excluded according to a previous study. 14 The following clinical data were extracted from the database: patients' unique identifiers; patients' backgrounds; comorbidities before admission; consciousness level on admission according to the Japan Coma Scale (JCS); treatments performed in the hospital, including operations, drugs, and additional treatments; length of hospital stay; total medical cost; and outcomes including in hospital death and ADL at discharge according to Barthel Index (BI). Diagnosis and comorbidities were primarily defined on the basis of the ICD-10 codes, but they were also checked to examine whether these were compatible with the code data.…”
Section: Study Participantsmentioning
confidence: 99%
“…During the past decades, the incidence of rAA is believed to have decreased because of primordial prevention (decreased prevalence of risk factors), primary prevention (population screening programs and elective repair), and improvement in surgical care for ruptured aneurysms. 4,5 A recent study has shown a decrease in ruptured abdominal aortic aneurysm (rAAA)-related hospitalizations from 21 to 16 per 100,000 persons in England and from 10 to 7 per 100,000 persons in the United States. 6 Despite that, aortic aneurysms and dissection were ranked as the 15th leading cause of death for people aged 65 years and older in the United States.…”
mentioning
confidence: 99%